A STUDY OF COMMUTER LINE SOCIAL PRACTICE ON ANTHONY GIDDENS’ STRUCTURATION THEORY - Sylvia Savitri; Naswan Iskandar (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2018)
One of factors which lead to the evolutionary social changes in Indonesia is thetransformation of mass transportation, such as commuter line. Commuter line helpsto bring a modification that emerges through a media of agency and structure.Various regulations, ranging from coercive to structural ones, have been modifiedand fully obeyed by the passengers of commuter line. A structure, rules, regulations,and monitoring activities are the practical principles as well as the means for anongoing process of social practice of the commuter line passengers. A criticalexamination of this case is embodied in structuration theory which covers two centralthemes of Giddens’ (2010) pivotal ideas: the relationship between the structure andagency, the centrality of space and time. The analysis concludes that socialtransformation, although not complete, may occur if there is a complementaryrelationship or duality between an agency and a structure.